Three-ray path loss based on peak power loss for ultra wideband impulse radio systems - Supanakoon, Pichaya; Chaiyapong, Saksit; Promwong, Sathaporn; Takada, Jun Ichi (My University, 2011)
Path loss is important parameter to analyze and design link budget. For indoor environment, there is fading that occurs in path loss. Therefore, accurate path loss model, which is considered fading, is necessary. In this paper, three-ray path loss based on peak power loss is proposed for ultra wideband impulse radio (UWB-IR) systems. The rectangular passband is used as UWB-IR transmitted signal. The extension of Friis' transmission formula is applied for UWB-IR three-ray channel. The received signal is evaluated. The closed form formula of three-ray path loss is derived based on peak power loss. The path loss from proposed model was illustrated and compared with three-ray model based on average power loss and free space model. This model can be used to study the characteristic of fading and extended to multi-ray path loss model for indoor environment. © 2011 IEEE.
Keywords: path loss; Three-ray model; ultra wideband impulse radio (UWB-IR)